On + voir dans la traduction polonaise - Skibińska, Elżbieta (Neophilologica, 2006)
In her article Elżbieta Skibińska examined, on the example of three novels by Georges Simenon and their Polish translations, the possible interpretations and Polish renderings of the on + voir construction. Even such a limited linguistic corpus allowed the author to distinguish two ways of translating this construction: the first one, with the use of the predicate widać (one can see that...), retains the element of the visual perception; the second one, based on the use of a verb that can position an object in space, stać, leżeć, wisieć etc. (stand, lie, hang), eliminates the element of the visual perception. The outcome of the analysis made the author formulate the hypothesis that perceptional depiction of the presented events happens more often in French than in Polish, but this hypothesis ought to be verified on broader material.